Organosolv pulping of Oil Palm Frond (OPF): effect of beating on pulp and paper properties - Mohd Jamal, Mohd Abdul Hafiz; Mohd Nordin, Muhammad Norsyahir; Samsuddin, Mohd Izwan Sharmimi (2012)
The research was done to identify the effect of pulping and paper properties based on differences effect of beating which tensile test has shown 24.69% at zero beating,35.80% at 1000 beating and 39.51% at 2000 beating. For tear test, at zero beating has 26.67% ,for 1000 beating has 40% and for 2000 beating has 33.33%. For freeness test, zero beating has shown 33.61%, for 1000 beating has 33.42% and for 2000 beating has 32.97%. The result showed significant different on tensile and tear test but not significant for freeness test.